Factors influencing small and medium enterprises’innovativeness: Evidence from manufacturing companiesin Harare, Zimbabwe - Charles Makanyeza; Blessing Kudzai Mabenge; Grace Portia Kuda Ngorora-Madzimure (Wiley, 2023)
The study investigated factors influencing innovativeness in small and medium enterprises (SMEs). Using empirical data from 330 SMEs, structural equation modelling was employed to test the factors that influence innovativeness at the level of the firm, namely the firm's resources, government support and institutional policies, networks and collaborations, the organization's innovative culture, local knowledge diffusion, and facilitating conditions. Results show that the firm's resources, government support and institutional policies, and networks and collaborations each positively influences innovativeness at the level of the firm. On the contrary, the organization's innovative culture, local knowledge diffusion and facilitating conditions were found to have insignificant effects on innovativeness. It is recommended that, to increase innovativeness, SMEs should invest in building up their resources in terms of both tangible and intangible resources. They can also lobby the government for support and to institute policies that promote innovativeness. Furthermore, SMEs are advised to build networks and collaborations with other institutions such as colleges, universities, research institutions and well-established and innovative firms. SMEs in developing and emerging markets can benefit from these findings.